APG III: Bibliographical Information and Synonymy of Magnoliidae - Reveal, J. L.; Chase, M. W. (Phytotaxa, 2011)
An updated classification of the orders and families of flowering plants was published in 2009 by the Angiosperm Phylogeny Group along with two companion papers, one a linear arrangement of the taxa, and a second treating the land plants above the rank of order. These papers are combined with full synonymy and bibliographic information along with an index to the names.